The Narrative Functions of Clothing in the Book of Joshua - Hamlin, Allan (Language and Linguistics E-Books Online, Collection 2026., 2026)
Why do terse Hebrew Bible narratives bother to mention clothing? Often presented without description nor overt contribution to plot, why were these references retained in the final forms of these stories? Through the use of a multifaceted analytical toolkit this study exhaustively examines the five clothing pericopes in the book of Joshua. Embedding each text in its various layers of context, you will observe a trope of evolution of identity carried along by sartorial language and discover the unobtrusive contributions made to characterisation, such as Joshua's divergence from Moses in removing a single sandal to demonstrate the acquiescence of his rights and his posture of subservience as YHWH's conquest commander. Close reading of each text is supported by colourised clausal-analysis charts which enable an appreciation of the rich information encoded in the narratively significant disjunctive Hebrew Masoretic accents.